2017
DOI: 10.1158/1078-0432.ccr-16-0712
|View full text |Cite
|
Sign up to set email alerts
|

U.S. FDA Approval Summary: Nivolumab for Treatment of Unresectable or Metastatic Melanoma Following Progression on Ipilimumab

Abstract: On December 22, 2014, the FDA granted accelerated approval to nivolumab (OPDIVO; Bristol-Myers Squibb) for the treatment of patients with unresectable or metastatic melanoma and disease progression following ipilimumab and, if BRAF V600 mutation positive, a BRAF inhibitor. Approval was based on a clinically meaningful, durable objective response rate (ORR) in a non-comparative analysis of 120 patients who received 3 mg/kg of nivolumab intravenously every 2 weeks with at least 6-month follow-up in an ongoing, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 5 publications
1
69
0
Order By: Relevance
“…found in a complementary analysis that the maximum decrease in nivolumab clearance was statistically associated with baseline disease status and hinted that posttreatment disease status may also play a role in nivolumab exposure. None of the covariates were found clinically relevant and the same conclusion was reached in the analysis described in the approval summary . While this analysis focused on the 3 mg/kg q2w (every 2 weeks) dosing regimen, a subsequent study supported the use of 240 mg q2w …”
mentioning
confidence: 62%
“…found in a complementary analysis that the maximum decrease in nivolumab clearance was statistically associated with baseline disease status and hinted that posttreatment disease status may also play a role in nivolumab exposure. None of the covariates were found clinically relevant and the same conclusion was reached in the analysis described in the approval summary . While this analysis focused on the 3 mg/kg q2w (every 2 weeks) dosing regimen, a subsequent study supported the use of 240 mg q2w …”
mentioning
confidence: 62%
“…One approach relies on single-arm or small non-comparative phase II trials (e.g. (12)); others transition seamlessly from phase I trial to multi-cohort expansion phase or basket trial in specific histologies. These studies seek accelerated approval by meeting the US Food and Drug Administration (FDA) criteria for unmet medical need based on a surrogate endpoint, such as objective response rate (ORR).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer immunotherapy has become a focus of investigation, including research into immune checkpoint inhibitors (ICIs). Programmed death (PD) 1 inhibitors such as nivolumab or the cytotoxic T‐lymphocyte‐associated antigen (CTLA) 4 inhibitors such as ipilimumab have been approved by the US Food and Drug Administration (FDA) . Several phase III randomized controlled trials (RCTs) have concluded that monotherapy with these agents can exert robust antitumor effects.…”
mentioning
confidence: 99%